"Put it in Your Toolbox": How Vocational Programs Support Formerly Incarcerated Persons through Reentry - Towne, Katelynn (Crime & delinquency, 2023)
This study utilized life story interviews with 21 formerly incarcerated individuals to examine the role vocational reentry programming played in the desistance process. We begin with a review of theories of desistance and the state of reentry programs. A thematic analysis revealed that providers assisted individuals to understand their behavioral trajectories and to take steps toward desistance. Further, participants felt empowered by program provided social support, developed strategies to overcome employment barriers, and held resilient and optimistic attitudes in changing their identities and behavioral trajectories. We conclude with a discussion on how these findings can inform desistance theory and reentry policy.